ANALYSIS OF THE IMPACT OF CHANGES IN LICENSING LEVY RATES ON MANDATORY LEVY COMPLIANCE AND BANGKALAN REGIONAL ORIGINAL INCOME - Moh. Riski Maulana; Lailatul Qomariyah; Julliatin Puspita Sari; Akmal farhan Tito rahmatulloh; Mohamad Djasuli (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research aims to analyze the impact of changes in licensing levy rates on mandatory levy compliance and its contribution to Regional Original Income (PAD) in Bangkalan Regency. The background to this study stems from fluctuations in the contribution of levies to PAD and indications of a decline in compliance after the implementation of adjustments to levy rates regulated through the 2023 Regional Regulations. This research uses a descriptive qualitative approach with a literature study method, utilizing secondary data from national regulations, regional government documents and scientific literature. The research results show that changes in tariffs have not had a significant impact on increasing PAD. Based on DPMPTSP Bangkalan data, it was recorded that there was a decrease in the number of mandatory levies for processing certain permits after the implementation of the new tariff, with an estimated decrease. Lack of socialization, inadequate public services, and low community participation are the main obstacles in implementing policies. This research recommends a strategy for optimizing levies through potential mapping, digitizing services, regulatory reform, strengthening supervision, and a participatory approach so that levy policies are more effective, responsive and sustainable.